Interrelationship of Mental Health and Self- Confidence Performance Athlete Badminton PB Tugu Muda Semarang - Deafiga, Fadiga Nazario Aimar; Sungkowo, Sungkowo; Ramadhan , Indra (Universitas Negeri Semarang, 2025)
This research aims to understand the connection between mental health and confidence self with achievement athlete badminton PB Tugu Muda Semarang. Sample in this research consists of of 30 athletes, consisting of over 21 athletes son and 9 athletes daughter. The analysis method used was the Spearman correlation test, because the data did not fulfill the assumption normality. Research results show existence connection significant negative between Mental Health and achievement (r = -0.536; p = 0.002), which indicates that the taller level mental health, then the lower performance athletes. On the other hand, there are connection significant positive between trust self and achievement (r = 0.551; p = 0.002), which means the taller trust self-athlete, then the better achievements are also achieved. Most of them athlete is at in category currently until high on aspects mental health and confidence self. The results of this research show importance development of training programs that are not only focus on aspects technical and physical, but also on the aspects psychological, especially trust self and mental readiness, in order to support achievement optimal performance.